SISTEM KENDALI ROBOT PENGINTAI MENGGUNAKAN KONTROL KOMPUTER BERBASIS MIKROKONTROLER ARDUINO - Al Hafiz Amrillah; Hastha Sunardi; Zulkifli Zulkifli (Jurnal Informatika Global)
In general, the robot can be defined as a mechanical device that can do the work of man or behave like a human, one human work that can be carried out reconnaissance activities against the robot is something that becomes the object of man's purpose. Surveillance robot is designed to be able to perform the task of staking something, for the robot is equipped with a wireless camera that is connected to the computer as a indicator of the object captured by the camera, the robot is also equipped with a remote as motion control of the robot, the robot is equipped with a program to guide the process the work of the robot. At the time of power supply in the On the the program that is loaded on the arduino executed, and the camera is active, ready to capture the object in front of him, the robot will move according to the command through the remote as a controller, the object of which was caught on camera transmitted via wireless signals to a PC to be translated as a moving image, until the power supply in this reconnaissance matikan.robot bekerka on a plane and not berpenghalang, the robot can not work well if it passes through an area with a certain angle and has a barrier.